Su(H)-Mediated Repression Positions Gene Boundaries along the Dorsal-Ventral Axis of Drosophila Embryos. - Ozdemir, A.; Ma, L.; White, K.P.; Stathopoulos, A. (Developmental Cell, 2014)
In Drosophila embryos, a nuclear gradient of the Dorsal (Dl) transcription factor directs differential gene expression along the dorsoventral (DV) axis, translating it into distinct domains that specify future mesodermal, neural, and ectodermal territories. However, the mechanisms used to differentially position gene expression boundaries along this axis are not fully understood. Here, using a combination of approaches, including mutant phenotype analyses and chromatin immunoprecipitation, we show that the transcription factor Suppressor of Hairless, Su(H), helps define dorsal boundaries for many genes expressed along the DV axis. Synthetic reporter constructs also provide molecular evidence that Su(H) binding sites support repression and act to counterbalance activation through Dl and the ubiquitous activator Zelda. Our study highlights a role for broadly expressed repressors, like Su(H), and organization of transcription factor binding sites within cis-regulatory modules as important elements controlling spatial domains of gene expression to facilitate flexible positioning of boundaries across the entire DV axis.